2019
DOI: 10.1007/s00216-019-01622-7
|View full text |Cite
|
Sign up to set email alerts
|

Programmable RNA-based systems for sensing and diagnostic applications

Abstract: The emerging field of RNA nanotechnology harnesses the versatility of RNA molecules to generate nature-inspired systems with programmable structure and functionality. Such methodology has therefore gained appeal in the fields of biosensing and diagnostics, where specific molecular recognition and advanced input/output processing are demanded. The use of RNA modules and components allows for achieving diversity in structure and function, for processing information with molecular precision, and for programming d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…Compared with proteinbased transcriptional and translational regulation, 30 the use of RNAs has several advantages, including their easily predictable base-pairing interactions, dynamic binding-induced conformational changes, and the ability of systematically evolving new ligand-recognition units, e.g., aptamers. 31 To date, a couple of RNA-based designs have been developed into powerful gene regulation devices both in vitro and in vivo. [32][33][34][35][36] In this section, we will focus on artificially designed genetically encoded RNA nanodevices that have been validated inside living cells for gene expression and regulation.…”
Section: Genetically Encoded Rna Nanodevices For Gene Regulationmentioning
confidence: 99%
“…Compared with proteinbased transcriptional and translational regulation, 30 the use of RNAs has several advantages, including their easily predictable base-pairing interactions, dynamic binding-induced conformational changes, and the ability of systematically evolving new ligand-recognition units, e.g., aptamers. 31 To date, a couple of RNA-based designs have been developed into powerful gene regulation devices both in vitro and in vivo. [32][33][34][35][36] In this section, we will focus on artificially designed genetically encoded RNA nanodevices that have been validated inside living cells for gene expression and regulation.…”
Section: Genetically Encoded Rna Nanodevices For Gene Regulationmentioning
confidence: 99%
“…Excellent recent reviews survey these and other variations of monolithic switches. [69][70][71] Both type 1and 2 switches are compatible with intracellular applications.I nspired by the work of Breaker on ribozymes, [72] structural aptameric switches of type 1w ere proposed by Stojanovic et al [73] Hammond and colleagues fused naturally occurring aptamers (riboswitches) with Spinach aptamer for the detection of cyclic di-GMP and cyclic AMP-GMP. [74][75][76] Recently, genetically encoded Spinach type 1switches were applied for the intracellular detection of metabolites in live cells.…”
Section: Blas Designmentioning
confidence: 99%
“…[64] Introduced by Stojanovic et al, [63] this approach has found several implementations for ad iverse spectrum of analytes. [64][65][66][67][68][69][70][71] This design shares the "advantage of being split" of the binary light-up aptameric sensors:a ssay optimization is simplified (see above). Thedisadvantage of split aptameric sensors is the need for the covalent labeling of strands 1a nd 2w ith af luorophore and quencher, and purification of such conjugates,w hich 1) increases the cost and reduces the yield of synthetic oligonucleotides,a nd 2) makes this approach incompatible with sensor expression in live cells for intracellular imaging.…”
Section: Figure 2bmentioning
confidence: 99%
“…If a fluorescence quencher is used, the signal can be represented as a Förster resonance energy transfer (FRET) [64] . Introduced by Stojanovic et al., [63] this approach has found several implementations for a diverse spectrum of analytes [64–71] . This design shares the “advantage of being split” of the binary light‐up aptameric sensors: assay optimization is simplified (see above).…”
Section: Blas Designmentioning
confidence: 99%
See 1 more Smart Citation